DAMPAK KONVERGENSI IFRS TERHADAP COST OF EQUITY CAPITAL - Rahayu Widati; Ari Budi Kristanto (AKUNTANSI DEWANTARA, 2018)
This study aims to examine the impact of IFRS adoption on cost of equity capital in manufacturing companies listed at Indonesian capital market, during 2008-2016. This study uses the proxy of capital asset pricing model in assessing cost of equity capital and using multiple regression to test the relation between variables. The research results proved that IFRS convergence negatively affect the cost of equity capital. Therefore, it can be concluded that by adopting IFRS, can reduce the cost of equity capital.